Feminist Identity: The Feministic Identity Development Scale, psychometrical and adaption in environment of Latvia - Dombrovskis, Aivis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The feminism is becoming more popular in Latvia now, but it’s impossible to find some psichological instrument which is adapted in latvian language and which is useabled for measuring the charecteristic’s of feminist identity. In this article are displayed the Feministic Identity Development Scale (FIAS- in latvian) (the origional inquiry :Feministic Identity Development Scale (FIDS), Bargad & Hyde, 1991), thous diferent versions of their adaption and also versions of their modifications; Cronbach’s Alpha from 0.5 to 0.8, and their version in latvian language.The adaptation of FIAS took part in three stages, the sample of the research consists only from women. The first sample consists form 330 women in age from 18 to 27 (M=18,75; SD=1,06) years old. The second and third sample consist form 501 women from 18 to 27 (M=20,33; SD=1,94) years old. The sample of Test- retest: 30 respondents. In the course of the instrument adaptation in the psychometrical analysis was appointed: the summary of FIAS factorial modification version, the factorial validity, the analysis of the affirmatory factors, the convergential and divergential validity of FIAS.The results gained in the course of inguiry the factorial modification version of FIAS- are acknowledged to be acceptable and instruments of the inguiry of the identity crisis – approved to be useful for futher usage in investigation and can be practically used for psychological researches in Latvia.